The identification of surface proteins of Burkholderia pseudomallei. - Harding, S; Sarkar-Tyson, M; Smither, S; Atkins, T; Oyston, P; Brown, K; Liu, Y; Wait, R; Titball, R (2007)
Burkholderia pseudomallei, the causative agent of the disease melioidosis is a human pathogen endemic in Northern Australia and South-East Asia. At present there is no available vaccine or effective treatment for this disease. Surface proteins play crucial roles in the host-pathogen interaction and have been exploited as vaccine candidates and diagnostic targets. Therefore, we wished to identify immunogenic surface proteins of B. pseudomallei. To this end we used two proteomic-based approaches in parallel: a biotinylation approach for the detection of surface located proteins identified 35 proteins, while screening with human sera identified 12 immunogenic proteins. Nine of these proteins were identified by both methods indicating that they may be both surface located and immunogenic: these proteins will be evaluated further as vaccine candidates and diagnostic targets.